Effect of Liquidity and Solvability Ratio on Profitability - Yeti Kusmawati (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aims to determine the effect of liquidity and solvency on profitability at PT. Antam Tbk Period 2011-2018. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Current Ratio did not significantly influence the Return on Investment of 23.9%, the hypothesis test obtained a significance value of 0.219> 0.05. Debt To Equity Ratio has a significant effect on Return on Investment of 70.1%, the hypothesis test obtained a significance value of 0.009 <0.05. Current Ratio and Debt To Equity Ratio simultaneously have a significant effect on Return on Investment obtained regression equation Y = 28,859 - 0,007X1 - 0,585X2 and the determination value of 70.7%, the hypothesis test obtained a significance value of 0.046 <0.05.